(untitled) (Journal of the College of Basic Education, 2022)
This study aimed at extracting bacteriocin produced from Lactobacillus plantrum isolated from 30 samples, including yoghurt, local cheeses and Activia yoghort. The isolates were selected based on their ability to produce bacteriocin and its inhibitory effect on some pathogenic bacteria. This study included the extraction of bacterium Influence on H.pylori bacteria isolated from the stomach of patients and transformers to the Department of Gastroenterology at Yarmouk Hospital for the period from 20/2/2015 to 10/9/2015.The results of our culture and microscopic study and biochemical diagnostic tests performed on isolates showed that five isolates of L.plantrum had the ability to produce bacteriocin differently depending on the isolates and were extracted purely. The study improved the ability of bacteriocin to inhibit the growth of H.pylori bacteria and urease enzyme at concentration used, The effect of bacteriocin was studied based on bacteriocin inhibition